COVID-19 and other pandemics : a comparison - Nardo, Don, 1947- (ReferencePoint Press, 2021)
"Similarities between human reactions to onslaughts of deadly diseases separated by millennia illustrates the morbid universality of such outbreaks. It reminds us that large attacks of lethal germs are nothing new, nor are human reactions to them. One problem inherent in such pandemics is that over time people tend to forget the lessons of past"--